Excitonics of semiconductor quantum dots and wires for lighting and displays - Guzelturk, Burak (2014)
In the past two decades, semiconductor quantum dots and wires have developed into new, promising classes of materials for next-generation lighting and display systems due to their superior optical properties. In particular, exciton–exciton interactions through nonradiative energy transfer in hybrid systems of these quantum-confined structures have enabled exciting possibilities in light generation. This review focuses on the excitonics of such quantum dot and wire emitters, particularly transfer of the excitons in the complex media of the quantum dots and wires. Mastering excitonic interactions in low-dimensional systems is essential for the development of better light sources, e.g., high-efficiency, high-quality white-light generation; wide-range color tuning; and high-purity color generation. In addition, introducing plasmon coupling provides the ability to amplify emission in specially designed exciton–plasmon nanostructures and also to exceed the Förster limit in excitonic interactions. In this respect, new routes to control excitonic pathways are reviewed in this paper. The review further discusses research opportunities and challenges in the quantum dot and wire excitonics with a future outlook.